Bank efficiency in China, rent seeking versus X-inefficiency: A non-parametric bootstrapping approach - Kent Matthews; Jianguang Guo; Nina Zhang; Lina Wang (Cardiff University, Cardiff Business School, 2007)
This study demarcates cost-inefficiency in Chinese banks into X-inefficiency and rent-seeking-inefficiency. A protected banking market not only encourages weak management and X-inefficiency but also public ownership and state directed lending encourages moral hazard and bureaucratic rent seeking. This paper uses bootstrap non-parametric techniques to estimate measures of X-inefficiency and rent-seeking inefficiency for the 4 state owned banks and 11 joint-stock banks over the period 1997-2004. In contrast to other studies of the Chinese banking sector, the paper argues that reduced inefficiency is an indicator that the competitive threat of the opening up of the banking market in 2007 has produced tangible bene fits in improved performance. This paper finds evidence of declining trend in both types of inefficiency.
Keywords: D23; G21; G28; 330; Bank Efficiency; China; X-inefficiency; DEA. Bootstrapping; Bank; X-Effizienz; Rent Seeking; Data-Envelopment-Analyse; China